1:01 Wabash Railroad Depot; 300 West McPherson; Kirksville Photos by Drake, 1893: The Clifford Henry Album (MUSDP K1) - Drake (Drake, Fotografer, 1893)
The North Missouri Railroad, which began north-south passenger and freight service through Kirksville in 1868, became part of "The Wabash Line" in 1889. This building, on the west side of the track at the corner of McPherson and First Streets, was the Road's first depot. It survived one fire in 1885 and was extensively damaged again when a lamp exploded in the freight room on the evening of Saturday, June 1, 1895. Singed but still somewhat usable, the rest of the building remained open until the new depot at Washington and First Streets was completed later that year.